2015
DOI: 10.1620/tjem.236.209
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Umbilical Cord Mesenchymal Stem Cells for Inhibiting Myofibroblastic Differentiation of Irradiated Human Lung Fibroblasts

Abstract: Radiation-induced lung injury (RILI) limits the benefits of radiotherapy in patients with lung cancer. Radiation-induced differentiation of lung fibroblasts to myofibroblasts plays a key role in RILI. Recent studies have shown that mesenchymal stem cells (MSCs) can protect against lung fibrosis and that Wnt/ β-catenin signaling is involved in fibrotic processes. In the present study, we explored the therapeutic potential of human umbilical cord MSCs (HUMSCs) for preventing radiation-induced differentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
(49 reference statements)
2
19
0
Order By: Relevance
“…The CD11c + DCs, derived from UCB, are morphologically and phenotypically similar to those of peripheral blood derived CTLs-DCs, suggesting that UCB-DCs can be used for personalized medicine of cancer patient, in need for DCs transplantation [ 103 ]. Coculture of UCSCs with radiation exposed human lung fibroblast stops their transdifferentiation, which suggests that factors secreted from UCSCs may restore niche identity of fibroblast, if they are transplanted to lung after radiation therapy [ 104 ]. Tearing of shoulder cuff tendon can cause severe pain and functional disability, whereas ultrasound guided transplantation of UCB-MSCs in rabbit regenerates subscapularis tendon in four wks' time frame, suggesting that UCB-MSCs are effective enough to treat tendons injuries when injected to focal points of tear-site [ 68 ].…”
Section: Ucscs In Regenerative Medicinementioning
confidence: 99%
“…The CD11c + DCs, derived from UCB, are morphologically and phenotypically similar to those of peripheral blood derived CTLs-DCs, suggesting that UCB-DCs can be used for personalized medicine of cancer patient, in need for DCs transplantation [ 103 ]. Coculture of UCSCs with radiation exposed human lung fibroblast stops their transdifferentiation, which suggests that factors secreted from UCSCs may restore niche identity of fibroblast, if they are transplanted to lung after radiation therapy [ 104 ]. Tearing of shoulder cuff tendon can cause severe pain and functional disability, whereas ultrasound guided transplantation of UCB-MSCs in rabbit regenerates subscapularis tendon in four wks' time frame, suggesting that UCB-MSCs are effective enough to treat tendons injuries when injected to focal points of tear-site [ 68 ].…”
Section: Ucscs In Regenerative Medicinementioning
confidence: 99%
“…In in vivo and in vitro studies, MSCs were found to alleviate irradiation-induced lung injuries not only by the secretion of cytokines, growth factors, and paracrine molecules but also by immunomodulatory effect. Moreover, they could modulate immune response, attenuate inflammation, and regulate the release of proinflammatory and profibrotic molecules involved in fibroblast proliferation and extracellular matrix excess deposition [2, 1113]. Some previous studies also demonstrated that MSCs act as gene therapy delivery vehicles and attenuate lung injury through enhancing the target gene expression in specific damaged tissue sites in the lungs [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Myofibroblasts can further promote the synthesis of additional collagens, leading to excessive deposition and abnormal remodeling of the extracellular matrix, which is a hallmark of RILI . Zhang et al reported that human umbilical cord MSCs (hucMSCs) can attenuate RILI by inhibiting myofibroblastic differentiation of human lung fibroblasts . However, whether the inhibition involves the secretome of MSCs was unclear.…”
Section: The Potential Of Msc Therapy For Rili Based On the Secretionmentioning
confidence: 99%